1992
DOI: 10.1128/aac.36.5.982
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 protease inhibitors irreversibly block infectivity of purified virions from chronically infected cells

Abstract: Synthetic peptide analog inhibitors of human immunodeficiency virus type 1 (HIV-1) protease were used to study the effects of inhibition of polyprotein processing on the assembly, structure, and infectivity of virions released from a T-celi line chronically infected with HIV-1. Inhibition of proteolytic processing of both Pr558w9 and Pr1609g W' was observed in purified virions from infected T cells after treatment. Protease inhibition was evident by the accumulation of precursors and processing intermediates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…This conclusion is in agreement with that of a previous biochemical report (35) and with morphological and structural analyses of both mature and immature HIV-1 virions by cryoelectron microscopy, which revealed a comparable density of Env proteins on both types of virions (4,53). Next, we examined whether Gag processing affects virus binding to target CD4 ϩ T cells.…”
Section: Fig 1 Prsupporting
confidence: 79%
“…This conclusion is in agreement with that of a previous biochemical report (35) and with morphological and structural analyses of both mature and immature HIV-1 virions by cryoelectron microscopy, which revealed a comparable density of Env proteins on both types of virions (4,53). Next, we examined whether Gag processing affects virus binding to target CD4 ϩ T cells.…”
Section: Fig 1 Prsupporting
confidence: 79%
“…Similar results obtained with viral RNA isolation from the particulate material of NCCIT cell culture medium and its subsequent quantification with RT-PCR amplification support this observation (data not shown). These data are consistent with the observation that HIV-1 protease inhibitors block the processing of Gag and Gag-Pol precursor polyproteins in HIV-1-infected cells but do not markedly alter either the number of particles released from the infected cells (44,45) or the amount of packaged viral RNA (46,47). In addition to using antigenspecific immunoblotting, we verified the identity of NCCIT released virions by checking the nucleotide sequence of packaged RNA.…”
supporting
confidence: 74%
“…Disruption of protease activity through site-directed mutagenesis (Kohl et al, 1988;Le Grice et al, 1988;Mous et al, 1988;Gottlinger et al, 1989) or inhibitor interaction (Kotler et al, 1988;Seelmeier et al, 1988) has been shown to result in improper processing of the viral polyproteins and the production of non-infectious virus particles. Since the protease functions at a late stage in the HIV life-cycle, protease inhibitors, unlike inhibitors of HIV reverse transcriptase (RT) , are effective against both productively infected cells and newly infected cells (Lambert et al, 1992).…”
Section: Introductionmentioning
confidence: 99%